2015
DOI: 10.3928/01477447-20151002-58
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Reverse Total Shoulder Arthroplasty in Patients Older Than 80 Years

Abstract: Anatomic total shoulder arthroplasty (TSA) and reverse total shoulder arthroplasty (RSA) are routinely performed in patients older than 80 years. Often unaware of the differences between the 2 procedures, patients may expect similar outcomes from these procedures. This article reports the outcomes of primary TSA and RSA in patients older than 80 years, with attention directed toward differences in outcomes between the procedures. The authors evaluated a consecutive series of patients who were at least 80 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…8,23 The outcome of RTSA in patients older than 80 years is underreported, with only a few studies in the current literature. 5,19,29 Recently, Clark et al 5 published a series of 179 patients, 81 of them personally followed up after primary RTSA mainly for cuff tear arthropathy (80%) and osteoarthritis (8%), and found satisfactory improvement in clinical outcomes and an acceptable surgical complication rate of 12%. The main complications were acromial fracture in 4%, delayed wound healing in 3%, and heterotopic ossification in 1.7%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,23 The outcome of RTSA in patients older than 80 years is underreported, with only a few studies in the current literature. 5,19,29 Recently, Clark et al 5 published a series of 179 patients, 81 of them personally followed up after primary RTSA mainly for cuff tear arthropathy (80%) and osteoarthritis (8%), and found satisfactory improvement in clinical outcomes and an acceptable surgical complication rate of 12%. The main complications were acromial fracture in 4%, delayed wound healing in 3%, and heterotopic ossification in 1.7%.…”
mentioning
confidence: 99%
“…The main complications were acromial fracture in 4%, delayed wound healing in 3%, and heterotopic ossification in 1.7%. Mangano et al 19 and Triplet et al 29 , studying 2 cohorts smaller than 33 patients with a followup between 24 and 87 months, reported promising improvement in clinical outcomes and a surgical nonsystemic complication rate of 10% and 15%, respectively. These complication rates resulted in very low reoperation rates between 0 and 2%.…”
mentioning
confidence: 99%
“…Complication rates are limited to 30-day outcomes, and although the use of RTSA is becoming more prevalent, CPT code 23472 was not able to separate reverse from anatomic arthroplasty. However, previous studies have found both anatomic TSA and RTSA to have similar complication rates, revision rates, and patient-reported outcomes, and this study focuses on short 30-day hospital quality metrics 15, 23, 33…”
Section: Discussionmentioning
confidence: 99%
“…Differences in indications for TSA and RSA likely contributed to this discrepancy, as patients undergoing RSA typically have pathologies, such as rotator cuff deficiency, that negatively influence preoperative baseline function. 30 In addition, age may have played a role in these differences, as TSA/TSA patients were significantly younger than TSA/RSA or RSA/ RSA patients. As one may expect, postoperative outcomes were found to be superior in this cohort compared with TSA/ RSA and RSA/RSA patients.…”
Section: Discussionmentioning
confidence: 99%